FITOKIMIA, DAN AKTIFITAS ANTIBAKTERI DARI Etlingera sublimata Poulsen (ZINGIBERACEAE), TUMBUHAN ENDEMIK SULAWESI: Phytochemical and Antibacterial Activity of Etlingera sublimata Poulsen (Zingiberaceae), Endemic Plant to Sulawesi - Ramadanil Pitopang; Endang Lestari; PUTI ANDALUSIA SARIGANDO Banilai; Wahyu Harso (Biology Department, Mathematics and natural science, Tadulako University, 2022)
The research entitled